Tafsir al-Muʿawwidzatayn Kyai Yasin Asmuni: Ideologi, Spiritualitas dan Pendekatan Hermeneutik - Wahyuni, Sri; Muhammad Abdullah Faqih (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This study examines the tafsir work al-Muʿawwidzatayn fī Bayān Faḍīlatihimā wa-Khawāṣṣihimā wa-Tafsīrihimā wa-Bayān al-Jinn wa-al-Shayāṭīn authored by Aḥmad ibn ʿAsmunī al-Jārūnī, a pesantren-based scholar from Kediri, Indonesia. The research aims to understand how this tafsir integrates pesantren traditions with Sufi spiritual dimensions. Employing a descriptive-analytical method and a Sufi hermeneutic framework, the study finds that al-Jārūnī’s interpretation represents a distinctive synthesis between textual understanding of Qur’anic verses and deep spiritual experience rooted in ascetic practice (riyāḍah). His tafsir exhibits a structured methodology grounded in classical references, enriched with mystical reflections that invite universal spiritual contemplation. In interpreting the al-Muʿawwidzatayn, al-Jārūnī emphasizes divine protection against the influence of jinn and devils, while also implicitly reinforcing Sunni theological positions. This work suggests that ideological elements in tafsir are not always hegemonic, but can serve as expressions of orthodoxy open to Sufi dialogue. The study concludes that this tafsir is an important contribution to the original and contextually relevant corpus of Nusantara Qur’anic exegesis. It reflects the dynamic nature of local interpretations that not only reproduce literal meanings but also transform the inner consciousness of readers. The study recommends further academic exploration of such local tafsir traditions to uncover the richness of Indonesian Islamic scholarship, which has often been overlooked in mainstream Qur’anic studies.